Hong Kong is a Science Fiction - Tammy Ho Lai-ming (Law Text Culture, 2014)
In the early 1980s, China’s state leader Deng Xiaoping put forward the scientific concept known as ‘one country, two systems’ in an effort ‘to realize the peaceful reunification of China’, and this ingenious design was first applied to solve the question of Hong Kong.